Correlation between Serum Sialic Acid Level and frequent risk factors of Diabetic Retinopathy - Rashid, Nada F. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Diabetic retinopathy is an important complication of diabetes mellitus. It is supposed that elevated sialic acid in diabetes mellitus plays an important role in diabetic retinopathy. This study investigated serum total sialic acid levels related to glycemic control, blood pressure, retinopathy, and serum lipid level in diabetic retinopathy patients. Patients & Methods: Type 2 diabetic patients aged (56.47±10.68) years were recruited for the study. Fasting venous blood samples were collected from 132 diabetic subjects of whom 79 without retinopathy and 53 were diabetic with retinopathy. All the blood samples were processed for serum total sialic acid (TSA), fasting serum glucose (FSG), HbA1c, and lipid profile. Systolic and diastolic blood pressure was recorded by standard mercury sphygmomanometer. Results: Serum (TSA), FSG, HbA1c, triglycerides (TG), and LDL-cholesterol were increased significantly (P<0.01 for TSA, FSG, HbA1c; P<0.05 for TG, and LDL) in patients with diabetic retinopathy (DR) compared to diabetics without retinopathy. Duration of diabetes and blood pressure were also significantly higher in DR patient compared to those without retinopathy. Correlation analysis showed a significant positive correlation between serum TSA and several risk factors of diabetic retinopathy: diabetic duration, FSG, HbA1c, systolic blood pressure SBP, diastolic blood pressure DBP, and LDL in diabetic patients with retinopathy. Conclusion: It is concluded that elevated serum total sialic acid level is strongly associated with the presence of diabetic retinopathy, a microvascular complication of diabetes. Increasing concentration of sialic acid is clinically correlated with several risk factors of diabetic retinopathy including glycemic control (blood sugar and HbA1c), hypertension, and duration of diabetes, triglycerides, and LDL. These findings strengthen the hypothesis that the increase in serum sialic acid is early manifestation of diabetic retinal disease.